Advances in Chitosan-Based Smart Hydrogels for Colorectal Cancer Treatment - Urszula Piotrowska; Klaudia Orzechowska (MDPI AG, 2024)
Despite advancements in early detection and treatment in developed countries, colorectal cancer (CRC) remains the third most common malignancy and the second-leading cause of cancer-related deaths worldwide. Conventional chemotherapy, a key option for CRC treatment, has several drawbacks, including poor selectivity and the development of multiple drug resistance, which often lead to severe side effects. In recent years, the use of polysaccharides as drug delivery systems (DDSs) to enhance drug efficacy has gained significant attention. Among these polysaccharides, chitosan (CS), a linear, mucoadhesive polymer, has shown promise in cancer treatment. This review summarizes current research on the potential applications of CS-based hydrogels as DDSs for CRC treatment, with a particular focus on smart hydrogels. These smart CS-based hydrogel systems are categorized into two main types: stimuli-responsive injectable hydrogels that undergo sol-gel transitions in situ, and single-, dual-, and multi-stimuli-responsive CS-based hydrogels capable of releasing drugs in response to various triggers. The review also discusses the structural characteristics of CS, the methods for preparing CS-based hydrogels, and recent scientific advances in smart CS-based hydrogels for CRC treatment.